"Cervical cancer screening: awareness is not enough". Understanding barriers to screening among women in West Cameroon-a qualitative study using focus groups. - Alida Manoëla Datchoua Moukam; Muriel Samartha Embolo Owono; Bruno Kenfack; Pierre Vassilakos; Patrick Petignat; Jessica Sormani; Nicole C. Schmidt (BMC, 2021)
Plain Language Summary Cervical cancer is the second leading cause of cancer-related death among women in sub-Saharan countries, constituting a major public health concern. In Cameroon, cervical cancer ranks as the second most common type of cancer among women and is the leading cause of cancer-related deaths, mainly due to the lack of prevention measures, such as cervical cancer screening. The main aim of the current study was to understand barriers that affect women's decision-making processes regarding participation in a cervical cancer screening program in the Dschang district in West Cameroon. A qualitative study methodology using focus group discussions was conducted from February to March 2020. Female participants aged between 30 and 49 years and their male partners were invited to participate. In total, six discussion groups with 43 participants (31 women and 12 men) were conducted. The most important barriers were a lack of health literacy, limited access to the program because of cost and distance, and disrespectful treatment by healthcare workers. Our results identified three key areas for improvement: first, increasing health literacy; second, providing cervical cancer screening in rural areas; and third, training healthcare providers and community healthcare workers in better patient-provider-communication.